TIKTOK ONE AS A SUPER TOOL SUITE: PLATFORM POWER AND THE DISTRIBUTION OF PLATFORM TOOLS - Mahetaji, Kaushar; Nieborg, David B. (AoIR Selected Papers of Internet Research, 2026)
This paper explores how platform companies distribute software-based resources or “platform tools” strategically to accrue market power, securing a dominant position in diverse markets, and infrastructural power, extending and supplanting critical systems and services for cultural production. Using the toolkit TikTok One as a case study, I showcase how platform company TikTok distributes software-based resources to expand its organizational boundaries. I approach the empirical analysis of TikTok One by adapting methods from information systems, advocating that platform scholars frame platform tools as “boundary resources” that can be mapped using “unified modelling language” (UML) diagrams—visualizations particularly useful for recognizing the complexity of TikTok One and the distribution of platform tools as relational, contextual, and historical. The empirical analysis reveals that TikTok One supports TikTok’s rise by furthering the company's growth as a “multisided market” or its mediation of interactions between different user groups. It does so in two ways: (1) TikTok One increases the number and diversity of user groups (“sides”) and (2) TikTok One increases the number and kinds of interactions between the different user groups. In a nutshell, I argue that tool distribution through TikTok One is a strategy exploited by TikTok to drive growth and produce dependencies. In studying TikTok’s governance of platform tools, this case study helps unpack how TikTok first came to asymmetrically govern key software in the cultural industries—an understanding necessary to regulate platform growth and rupture platform dependencies.